AB1072 General Practitioner Perceptions of Methotrexate and anti-TNF Treatments: A Qualitative Study. (15th July 2016) - Berthet, E.; De Rosa, M.; Lopez, J.; Vorilhon, P.; Soubrier, M.; Mathieu, S.
Abstract : Background: The objective of rheumatic disease management is to achieve remission. Methotrexate (MTX) is the first-line treatment choice and tumor necrosis factor alpha antagonists (anti-TNFs) are used in case of MTX failure or intolerance. While these treatments are initially prescribed then renewed by rheumatologists, general practitioners (GPs) are often confronted with them during routine patient follow-up. Objectives: We sought to study the perceptions of GPs from Auvergne (a region of France) regarding MTX and anti-TNFs treatments in common daily practice. Methods: A qualitative study was carried out among 14 GPs following up patients receiving methotrexate and anti-TNFs. The semi-structured interviews were conducted between May and October, 2014. Thematic transversal analyses of the data were conducted by both the interviewer and an independent researcher. Each difference detected between them was discussed, then resolved by consensus. Results: Of the 285 physicians who completed a preliminary questionnaire, 31 consented to participate in the qualitative. A total of 14 interviews, sufficient to obtain data saturation, i.e., until no new data emerged, were conducted, lasting between 8 minutes and 1 hour, with a mean duration of 23 minutes 30 seconds. In total, 57% of the physicians interviewed were female and 42% of all practiced within 15km of a rheumatologist. The participating physicians were either young doctors (14%) or had over 20 years of experience (78%). Four principal themes were recognized in the analysis: the GP's role with regard to the patients, their experience and difficulties concerning these treatments, their opinions of therapeutic education programs, as well as the need for improvements in clinical practices. The physician's role consisted in renewing methotrexate prescription (10/14) and managing comorbidities via vaccination, for example (7/14). The GPs reported good tolerance (10/14) and efficacy (8/14) with the treatments. However, there was still concern over the immunosuppression and increased infection risk associated with these treatments, causing them to hesitate in using them. The difficulties especially concerned drug interactions and managing anti-TNF discontinuation in the event of infection (5/14), especially for rural-based practices with less easy access to specialists. All the physicians expressed a desire for a practical tool to be implemented aiding them to manage these treatments (10/14). Conclusions: All the physicians reported difficulties in their daily management of these treatments. Close collaboration between GPs and specialists thus appears essential for this management. GP training is also to be encouraged. Disclosure of Interest: None declared